2019
DOI: 10.3390/cancers11091234
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Anterior Commissure in Early Glottic Cancer (Tis-T2): A Review of the Literature

Abstract: Background: The impact of the anterior commissure (AC) involvement on prognosis in laryngeal cancer remains a topic of discussion with inconsistent results in the literature. This review examines AC involvement as a prognostic factor in patients with early glottic cancer (Tis–T2) treated with radiotherapy or transoral laser microsurgery (TLM). Methods: A systematic literature search was performed. Due to the heterogeneity of the data, no meta-analysis was implemented. Weighted averages were calculated if the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 70 publications
3
23
0
Order By: Relevance
“…Although it is widely acknowledged that the presence of AC involvement can have a negative impact on the oncologic outcomes of early glottic SCC, the results so far reported in the literature about its predictive value have been inconsistent, and have generated much debate [ 19 , 22 , 23 , 24 , 25 ]. Even though several reviews have analyzed this issue, none of them definitively solved the existing controversy of the prognostic value of AC involvement [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is widely acknowledged that the presence of AC involvement can have a negative impact on the oncologic outcomes of early glottic SCC, the results so far reported in the literature about its predictive value have been inconsistent, and have generated much debate [ 19 , 22 , 23 , 24 , 25 ]. Even though several reviews have analyzed this issue, none of them definitively solved the existing controversy of the prognostic value of AC involvement [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is widely acknowledged that the presence of AC involvement can have a negative impact on the oncologic outcomes of early glottic SCC, the results so far reported in the literature about its predictive value have been inconsistent, and have generated much debate [ 19 , 22 , 23 , 24 , 25 ]. Even though several reviews have analyzed this issue, none of them definitively solved the existing controversy of the prognostic value of AC involvement [ 19 ]. In fact, the unique AC anatomical characteristics make this laryngeal subsite a challenging area for adequate pretreatment endoscopic and imaging workup by either CT or MR (with a high incidence of false negatives adequately assessed only intraoperatively, after surgical resection, or at longer follow-up), difficult area for surgical resection due to laryngeal exposure, and prone to technical radiotherapy issues at the air–tumor interface within the AC due to its variable degree of vascularization, ossification, and three-dimensional conformation/development further complicating its proper management [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found that the clinical, binary variable on anterior commissure involvement (yes/no) had no significant impact on oncological outcomes, whereas the vertical involvement of the anterior commissure on imaging showed a significant impact on LC. The varying results found in the literature can be explained by the variations in clinical definition of the anterior commissure area, variation in the detail of the clinical, endoscopic, and radiological evaluation of the lesion in the preoperative setting, the distinctive features, and limitation of each therapeutic modality, the biological behaviors of the tumor, and variations in the rigor of the follow-up policy [40]. These factors, combined with the complicated anatomy of the anterior commissure, the involvement of this subsite may very well be too complex to be included as a binary variable (yes/no) [40].…”
Section: Discussionmentioning
confidence: 99%
“…13,18 Despite this, the conclusions are not unanimous and the role of the ACI continues to be controversial. 9,22 To date, there are no prospective reports in this regard, so the objective of this study was to analyze the differences in survival, local control, and organ preservation in T1b glottic SCC patients treated with CO 2 TOLMS according to the presence of ACI. The findings in relation to ACI in our population are similar to previous studies in which an affectation of 69% was found.…”
Section: Discussionmentioning
confidence: 99%